Non-Medical Goods Logistics Management at Annisa Maternity and Child Hospital, Pekanbaru, 2024: Manajemen Logistik Barang Non Medis di Rumah Sakit Ibu dan Anak Annisa Pekanbaru Tahun 2024 - Sando, Welly; Wahyudi, Arif; Devis, Yesica; Sonia P, Lam (Jurnal Olahraga dan Kesehatan (ORKES), 2025)
Non-medical logistics as supporting equipment in perfecting and completing services at the Hospital that are beneficial for patients and Hospital employees. Hospital logistics has functions that are summarized in the logistics cycle including planning, procurement and storage. The planning process has been said to be going well because it has been carried out in accordance with existing procedures, however, in the procurement and storage process there are obstacles that have not been implemented effectively. So it is interesting for researchers to look at the logistics management of non-medical goods at RSIA Annisa. The aim is to determine the logistics management of non-medical goods at the RSIA Annisa Pekanbaru in 2024. The method used is descriptive qualitative research. The research was carried out in April-May 2024 at the RSIA Annisa. The informants in this research were 5 people consisting of the Financial Manager, Logistics Coordinator, PJ Logistics, Secretariat and Spirituality, and PJ IPSRS. The results of this research show that the logistics management of non-medical goods at the RSIA Annisa in terms of human resource input is still insufficient, facilities and infrastructure are still inadequate. The planning process has gone well, the procurement process has gone well but there are still obstacles to stock shortages, the storage process has gone well but the warehouse storage space is still insufficient. Existing obstacles still need to be evaluated to improve better logistics management of non-medical goods in the general support section and non-medical logistics warehouse at the RSIA Annisa Pekanbaru.